(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reveals aspects of the relationship between tourism and sightseeing services. In particular, the target directions of excursion services, their main indicators and the existing information base at the tourist enterprise are described. The sightseeing services are highlighted by the organization of the signpost, as well as the signs needed for each excursion.